Energy efficiency finance programs: Best practices to leverage private green finance - Simon Retallack; Andrew Johnson; Joshua Brunert; Ehsan Rasoulinezhad; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2018)
A common struggle across energy efficiency programs is the creation of sustainable private sector markets that reduce the energy demand. The purpose of this study is to outline the best practice for achieving smart public programs that overcome the main energy efficiency challenges and leverage the private finance needed for deployment at scale. Our concluded program is based on an assessment of 10 case studies, interviews, and evaluations of past programs. The results revealed that strong policy frameworks should strengthen investment business cases with the right economic and regulatory drivers. Furthermore, more resources should support technical assistance. Activities such as awareness raising, pipeline generation, and derisking are essential to create sufficient demand and commitment. Besides, upskilling, equipping, and accrediting suppliers and technical advisors are critical to create a sustainable, scalable, and bankable pipeline.
Keywords: O13; P18; C90; 330; energy efficiency; financing energy programs; best practices